Cross-sectional study of pediatric pain prevalence, assessment, and treatment at a Canadian tertiary hospital. Issue 1 (1st January 2021) - Senger, Alex; Bryce, Rhonda; McMahon, Casey; Baerg, Krista
ABSTRACT: Background: Painful experiences are common among hospitalized children. Long-term negative biopsychosocial consequences of undertreated pain are recognized. Aims: The study benchmarks pain prevalence, assessment, and treatment as first steps to improve pain care in a Canadian tertiary hospital. Methods: Single-day audits were undertaken on the pediatric ward (PW), pediatric emergency department (ED), and maternal services (MS). Participants (child or caregiver proxy) reported hospital pain experiences in the preceding 24 h; medical records were reviewed for assessment and treatment. Results: Among 84 participants, pain prevalence ranged from 75% to 88%; mean pain intensity ranged from 5.7 to 6.5/10. Prevalence of moderate to severe pain was 78% on PW, 65% in ED, and 55% on MS; needle pokes were the most frequent cause of worst pain. Documentation of pain assessment varied by setting (PW, 93%; ED, 13%; MS, 0%). Documented maximum pain scores were significantly lower compared to participant report (mean difference 4.5/10, SD 3.1, P < 0.0001). A total 29% (6/21) of infants with heel lance or injection received breastfeeding or sucrose, and 29% (7/24) of participants receiving other needle procedures had documented or reported topical lidocaine use. All participants on MS underwent needle procedures. Conclusions: Pain is experienced commonly by infants and children in PW, ED, and MS. Pain assessment documentation is not routine and underestimates participant report. Evidence-based pain management strategies are underutilized. An institution-wide quality improvement approach is required to address pain care. Pain assessment and needle pain prevention and treatment should be prioritized in these pediatric acute care and newborn care settings.